Implementing a perinatal depression screening in clinical routine: exploring the patientʼs perspective = Einführung eines Screenings auf perinatale Depression als Teil der Schwangerschaftsvorsorge aus Sicht der Patientinnen - Trinh, Thuy Giang; Schwarze, Cornelia E.; Müller, Mitho; Götz, Maren; Haßdenteufel, Kathrin; Wallwiener, Markus; Wallwiener, Stephanie (Geburtshilfe und Frauenheilkunde, 2022)
Introduction: Perinatal depression (PND) is a frequently observed mental disorder, showing a prevalence of up to 20% and resulting in unfavorable maternal and neonatal outcomes. Targeted screening for PND offers the potential to identify and treat undiagnosed cases and help prevent its deleterious consequences. The aim of the present study was to evaluate participantsʼ personal attitudes and acceptance of a routine screening program for PND in pregnancy care, identify any potential underlying factors, and appraise the general perspective on perinatal mental health problems. Methods: In total, 732 women in their second trimester of pregnancy took part in a PND screening program that was incorporated in routine prenatal care using the Edinburgh Postnatal Depression Scale (EPDS) and completed a web-based survey on screening acceptance.Results: Participants viewed PND screening as useful (78.7%, n = 555/705), especially in terms of devoting attention to perinatal mental health problems (90.1%, n = 630/699), easy to complete (85.4%, n = 606/710), and without feelings of discomfort (88.3%, n = 628/711). Furthermore, women with previous or current mental health issues rated the usefulness of screening significantly higher, as did women with obstetric risks (p < 0.01 - p = 0.04). The final regression model explained 48.4% of the variance for screening acceptance. Conclusion: Patient acceptance for PND screening was high in our study cohort, supporting the implementation of screening programs in routine pregnancy care with the potential to identify, sensitize, and treat undiagnosed patients to reduce stigmatization and offer access to tailored dedicated PND care programs.